Magnetic properties of carbon nanotube poly(ether-ester) nanocomposites - Glenis, S.; V. Likodimos; Guskos, N.; Yarmis, D.; Zolnierkiewicz, G.; Szymczyk, A.; Lin, C.L. (Journal of Applied Physics, 2010)
The magnetic and electronic properties of composites consisting of oxidized multiwall carbon nantubes (MWNTs) dispersed in elastomeric poly(ether-ester) segmented block copolymer have been studied by means of electron spin resonance (ESR) and dc magnetization measurements. A marked reduction in the MWNT diamagnetic response is identified, indicative of substantial hole doping related to the oxygen functional groups on the oxidized carbon nanotube's surface. Both ESR and the static magnetization reveal considerable enhancement of the spin susceptibility due to an excessive increase in the density of paramagnetic defects, which are sensitive to the dynamical polymer relaxation and thus to the MWNT-polymer interfacial coupling. © 2010 American Institute of Physics.